MORALNE NORME KAO REGULATOR SPORTSKIH ODNOSA - Spasoje Bjelica (Montenegrin Sports Academy and Faculty for Sport and Physical Education, 2005)
Moral is one of the very old forms of social conscience, which have been progressively interiorized in the way of living of the community, as well as of the individuals. There are different comprehensions of the notion of moral. Here we will not let us involve into interpretation of these concepts, but, holding to the most acceptable concept of moral, we will emphasize that by moral one can consider the collection of norms, which determine behavior of people, as well as their notion of good and evil. Moral is a normative conscience, as well as a value attitude. Values represent standards, which govern our behavior, and the permanent belief that the specific way of behavior and existence is socially or personally desirable. Prof. dr